2002
DOI: 10.1097/00005373-200212000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Natural History of Below-Knee Deep Venous Thrombosis in High-Risk Trauma Patients

Abstract: Patients identified as high-risk by our practice management guideline had a 14.1% incidence of a BKDVT; 94.1% were diagnosed within the first 3 weeks of hospitalization. Proximal propagation occurred in 4.7% and led to changes in management. Serial duplex examination of the BKDVT alone, rather than systemic anticoagulation or IVC filter placement, appears to be a reasonable treatment alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Within 4 to 8 days, 4.7% of CVDVTs propagated to an above knee position and 1.2% of patients had a pulmonary embolism when not anticoagulated. 19 In contrast, patients with CVDVTs who receive therapeutic anticoagulation seem to show zero or minimal rates of proximal propagation or pulmonary embolus. 20,21 In our study 2 patients with calf vein DVTs developed CT scan confirmed pulmonary embolus (PE).…”
Section: Discussionmentioning
confidence: 99%
“…Within 4 to 8 days, 4.7% of CVDVTs propagated to an above knee position and 1.2% of patients had a pulmonary embolism when not anticoagulated. 19 In contrast, patients with CVDVTs who receive therapeutic anticoagulation seem to show zero or minimal rates of proximal propagation or pulmonary embolus. 20,21 In our study 2 patients with calf vein DVTs developed CT scan confirmed pulmonary embolus (PE).…”
Section: Discussionmentioning
confidence: 99%
“…autopsy, venography, compression duplex ultrasound, color flow Doppler imaging, magnetic resonance), 8,9,11,12,16,18,19,29,30 the extent of the examination, 12,31,32 the skill of the technician performing the examination, the experience of physicians interpreting the study, 19 the patient population being studied, associated risk factors, and prophylactic measures employed. [1][2][3][4][5][6][7][8]33,34 With these considerations in mind, reports of infrageniculate DVTs in trauma patients range from 3.8% to 40% 1,9,11 with propagation in different veins below the knee in 10% 9 and suprageniculate extension in 4.7% to 10.0%. 9,11 In the highest risk trauma patients the incidence of infrageniculate DVTs has been reported to be 14.1%, with suprageniculate propagation occurring in 4.7%.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,9 -14 Increasing attention has focused on the incidence and prevention of DVT in trauma patients. 11,[15][16][17][18][19][20] Trauma patients may be at a particularly high risk because they, more than most, are likely to experience multiple components of Virchow's classical thromboembolism triad (stasis, hypercoagulability, and venous wall injuries). 21 Trauma patients may have stasis from shock, immobilization, paralysis, severed or interrupted blood supplies, post injury hypercoagulability, and intimal damage as a result of direct tissue trauma.…”
mentioning
confidence: 99%
“…Temporary filters are an attractive option in this context, as long as they are safe and stable, can be left in place long enough to permit normalization of the thrombosis and anticoagulation problems and can then be removed in all circumstances, whether or not they have trapped a thrombus while in place [7]. The insertion of an inferior vena cava filter prophylactically reduces pulmonary embolism in patients at increased risk [4,5]. The decision to implant vena cava filters, either temporary or permanent, is difficult, especially in young patients [9], but the techniques for placement of inferior vena cava filters have undergone continued evolution from open surgical exposure of the venous insertion site to percutaneous insertion in most cases today [10].…”
Section: Discussionmentioning
confidence: 99%